Preparation method and application of porous double-layer spherical structure carbon material
By preparing porous double-layer spherical carbon materials, and using raw materials such as resorcinol and formaldehyde to form core-shell structures, the problem of low adsorption efficiency of existing carbon materials in Cr(VI) wastewater treatment is solved, and efficient Cr( VI) Adsorption and removal.
Patent Information
- Application Number
- CN202411307614.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-24
AI Technical Summary
When existing carbon materials treat Cr(VI) wastewater, the pollution is high during the activation process and the carbon material quality is consumed. The simple increase in specific surface area and porosity cannot effectively improve the utilization rate of pore structure, resulting in Cr(VI) adsorption efficiency. Low.
The preparation method of porous double-layer spherical carbon material is adopted, and the hydrothermal reaction is carried out by resorcinol and formaldehyde as carbon sources, combined with ammonia water and silicon source to form a porous double-layer spherical carbon material with core-shell structure, avoiding chemical activation. Improved pore structure utilization.
Complete adsorption of low-concentration Cr(VI) wastewater was achieved, with an adsorption rate of 77.59-99.58%. Without introducing other doping elements, the adsorption efficiency of Cr(VI) was significantly improved, and the residual concentration decreased after treatment. to zero.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental purification materials, and particularly relates to a preparation method and application of a porous double-layer spherical structure carbon material. Background Art
[0002] Chromium plays an important role in many industries, including fabric manufacturing, metal finishing, metallurgy, chrome plating, glass manufacturing, wood preservatives and ceramics, but the discharge of chromium-containing wastewater from these industries will pollute water and soil. There are two typical species of chromium in natural ecosystems, namely Cr(III) and Cr(VI). Due to its strong solubility and obvious oxidation tendency, Cr(VI) is very toxic. Water polluted by Cr(VI) has a strong carcinogenic effect on humans. Due to its high teratogenicity and carcinogenicity, my country has listed Cr(VI) as a first-class pollutant that needs to be strictly controlled. The treatment of heavy metal Cr(VI) wastewater is urgent (P Sharma, SP Singh, SK Parakh, YW Tong. Health hazards of hexavalent chromium (Cr(VI)) and its microbial reduction . Bioengineered ,2022 , 13(3), 4923−4938).
[0003] Adsorption is one of the simple and effective methods for treating Cr(VI) wastewater. At present, porous carbon materials are mostly used for direct adsorption of Cr(VI), and the high specific surface area and high porosity of porous carbon materials are used to capture Cr(VI) in wastewater. However, general carbon materials can only produce high specific surface area and high porosity through chemical activation. The activators generally used are strong alkali KOH and sodium oxalate, and the amount of activator is higher than the amount of carbon material. For example, Liang et al. used a certain amount of CSs-N mixed with 3 times the weight of KOH and activated it to prepare a N-doped carbon material with a high porous structure (H Liang, R Sun, B Song, Q Sun, PPeng, D She. Preparation of nitrogen-dopedporous carbon material by ahydrothermal-activation two-step method and its high-efficiency adsorption ofCr(VI). Journal of Hazardous Materials ,2020, 387 , 121987), the activation process is highly polluting and the mass of carbon materials will be greatly consumed during the activation process.
[0004] In addition, the above preparation strategy simply increases the specific surface area and porosity of the carbon material itself, but does not improve the utilization rate of the pore structure. Liang et al. mixed the carbon material with KOH and activated it at 800 ° C for 3 hours to prepare a porous honeycomb amorphous carbon material with a specific surface area of 1436.1 m 2 / g, but its maximum adsorption capacity for Cr(VI) is only 332.53mg / g (H Liang, B Song, P Peng, G Jiao, X Yan, D She. Preparation of three-dimensional honeycomb carbon materials and their adsorption of Cr(VI). Chemical Engineering Journal, 2019 , 367 , 9−16). At present, the basic research on the application of special morphology in Cr(VI) adsorption is still limited to spherical and hollow spherical structures. Li et al. 3 O 4 Introduced into mesoporous carbon nanospheres, a surface area of 547 m 2 / g, Fe-doped magnetic mesoporous carbon nanospheres, but their maximum adsorption capacity for Cr(VI) is only 87 mg / g ( Journal of Alloys and Compounds, 2017, 698, 20−26); Li et al. prepared a 2 / g of sulfur and nitrogen co-doped hollow carbon spheres, but its maximum adsorption capacity for Cr(VI) is only 434 mg / g (H Li, NLi, P Zuo, S Qu, W Shen. Efficient adsorption-reduction synergistic effectsof sulfur, nitrogen and oxygenheteroatom co-doped porous carbon spheres forchromium (VI) removal. Colloids and Surfaces A: Physicochemical andEngineering Aspects , 2021 ,618 ,126502). The hollow spherical structure has an inner cavity. The low concentration of Cr(VI) in the liquid in the inner cavity and the high concentration of Cr(VI) in the liquid outside the sphere form a concentration difference, which makes the Cr(VI) adsorption obtain a greater mass transfer driving force. However, as the adsorption process proceeds, the concentration of Cr(VI) in the liquid in the inner cavity gradually increases, and this mass transfer driving force gradually disappears. Therefore, designing and constructing a Cr(VI) material that has both a cavity structure and the ability to maintain a low concentration of liquid in the cavity for a long time has important scientific significance and good application prospects. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings and gaps in the prior art, the primary purpose of the present invention is to provide a method for preparing a porous double-layer spherical carbon material. The method improves the utilization rate of the pore structure of the carbon material itself from the perspective of morphology and structure, and prepares a special double-layer spherical carbon material.
[0006] Another object of the present invention is to provide a porous double-layer spherical carbon material prepared by the above method. The carbon material can have an excellent microscopic porous structure during the preparation process, and can reach a specific surface area of 248.84~830.38m without chemical activation. 2 / g, the overall structure maintains a complete double-layer spherical structure with a core-shell structure and good dispersion. The special structural composition can improve the pore utilization of the carbon material during the adsorption process. Without introducing other doping elements, it can completely adsorb and remove Cr(VI) in low-concentration Cr(VI) wastewater.
[0007] Another object of the present invention is to provide the use of the above-mentioned porous double-layer spherical structure carbon material for adsorbing Cr(VI) in wastewater. In the carbon material provided by the present invention, in each individual double-layer carbon sphere, the inner cavity can be regarded as a special place, the inner core in the inner cavity and the filamentous carbon skeleton on the surface of the inner core can maintain an absolute low concentration of Cr(VI) in the inner cavity liquid, so that the inner cavity liquid and the waste liquid outside the shell form a concentration difference, so that Cr(VI) spontaneously transfers to the inside of the double-layer carbon sphere, and is captured by the outer shell of the double-layer carbon sphere during the transfer process. This special structure can achieve complete adsorption of Cr(VI) in low-concentration Cr(VI) wastewater, and the residual concentration of Cr(VI) in the waste liquid is reduced to zero after complete adsorption.
[0008] The purpose of the present invention is achieved by the following technical solutions: A method for preparing a porous double-layer spherical carbon material comprises the following steps: (1) Mixing and stirring a carbon source and ammonia water, then adding a silicon source, and then transferring the reaction mixture to a hydrothermal kettle for hydrothermal reaction. After the reaction is completed, cooling and separating the product to obtain a brown powder; wherein the carbon source is resorcinol and formaldehyde solution, and the amount ratio of resorcinol, formaldehyde solution, ammonia water, silicon source and ethanol is 1 mass part: (1-3) volume parts: (4-10) volume parts: (2.5-7.5) volume parts: 125 volume parts, 1 mass part: 1 volume part = 1g / mL; (2) calcining the brown powder obtained in step (1) in a protective atmosphere to obtain a black powder; (3) The black powder obtained in step (2) is added to an alkaline solution for etching, and a hollow middle layer is formed after etching the silicon dioxide, thereby obtaining the porous double-layer spherical structure carbon material.
[0009] Preferably, in step (1), the carbon source and aqueous ammonia are mixed and stirred for 4-8 hours at room temperature.
[0010] Preferably, after adding the silicon source in step (1), stirring is continued for 22 to 26 hours, and then the reaction mixture is transferred to a hydrothermal kettle for hydrothermal reaction; the silicon source is tetraethyl orthosilicate.
[0011] More preferably, after adding the silicon source in step (1), stirring is continued for 24 to 26 hours, and then the reaction mixture is transferred to a hydrothermal kettle for hydrothermal reaction.
[0012] Preferably, the formaldehyde solution in step (1) is a 37 wt % formaldehyde aqueous solution containing 10-15 wt % methanol stabilizer.
[0013] Preferably, the hydrothermal reaction in step (1) is carried out at 100° C. for 24 hours.
[0014] Preferably, the first stage of the two-stage calcination in step (2) is calcined at 200°C for 2h, and the second stage is calcined at 600-800°C for 2h; the heating rate of the two-stage calcination is 3°C / min, the protective atmosphere is nitrogen, and the nitrogen flow rate is 50mL / min.
[0015] More preferably, the first stage of the two-stage calcination in step (2) is calcined at 200°C for 2h, and the second stage is calcined at 600-700°C for 2h.
[0016] Preferably, the alkaline solution in step (3) is a 2 mol / L NaOH solution, and the etching time is 24 h.
[0017] The present invention also provides a porous double-layer spherical carbon material prepared by the above method. The specific surface area can reach 248.84~830.38m 2 / g, and its morphology is a porous double-layer spherical carbon material with a core-shell structure, with an overall particle size between 200~500nm, a shell thickness between 50~100nm, and an inner core particle size between 10~50nm.
[0018] The application of the porous double-layer spherical structure carbon material provided by the present invention is specifically used for adsorption of Cr(VI) in water.
[0019] Experiments show that after adding 50 mg of the porous double-layer spherical carbon material of the present invention to a 100 mL, 50 mg / L Cr(VI) solution, adsorption equilibrium is reached in 48 hours, and the adsorption removal rate can reach 77.59-99.58%. After treatment, the residual Cr(VI) concentration can be reduced to 0.2-11.2 mg / L. However, the non-double-layer solid carbon spheres and hollow carbon spheres prepared with resorcinol and formaldehyde have adsorption removal rates of only 26.20% and 67.29% for Cr(VI) under the same conditions, and the residual concentrations of Cr(VI) after treatment are 36.9 mg / L and 16.35 mg / L, respectively.
[0020] The mechanism of the present invention is: The present invention uses resorcinol and formaldehyde as raw materials, and after the inner core is generated, a silicon source is added to generate a silicon dioxide layer in the middle of the carbon ball, and then the silicon dioxide is removed to generate a hollow layer in the middle to obtain a porous double-layer spherical structure carbon material. The specific formation process is: resorcinol and formaldehyde are first polycondensed in an alkaline solution (ammonia water gives alkalinity) to form a spherical inner core, and tetraethyl orthosilicate is added after a period of time. Since the speed at which tetraethyl orthosilicate generates silicon dioxide in an alkaline solution is much faster than the polycondensation reaction speed of resorcinol and formaldehyde, a silicon dioxide layer begins to be generated on the surface of the inner core. At about 1 to 2 hours, tetraethyl orthosilicate is completely reacted to form a silicon dioxide layer that tightly wraps the inner core. As the reaction time is extended, a large amount of resorcinol and formaldehyde remain in the solution, and the polycondensation reaction continues to occur. The reaction is completely completed after about 24 hours, and after hydrothermal, high-temperature activation, and removal of the silicon dioxide layer, a porous double-layer spherical structure carbon material with good dispersibility is finally formed.
[0021] The beneficial effects of the present invention are: (1) The porous double-layer spherical structure carbon material prepared by the present invention is composed of core-hollow layer-shell, and has good dispersibility. Its particle size range is 200~500nm, the inner core is a non-uniform spherical diameter of 10~50nm, the filamentous carbon skeleton on the surface of the inner core enters the hollow layer, the hollow layer is 20~250nm, and the wall thickness is 50~100nm. Compared with double-layer porous spherical structure carbon materials prepared by other methods, the inner core of the porous double-layer spherical structure carbon material prepared by the method of the present invention is not composed of a regular spherical structure, but is composed of a sea urchin-like inner core. The filamentous carbon skeleton on the surface of the sea urchin-like inner core is distributed in the entire middle hollow layer, and more liquid is in contact with the middle hollow layer, which makes it easier to capture hexavalent chromium in the hollow layer solution, thereby ensuring the absolute low concentration of the liquid in the hollow layer, enhancing the ability of the double-layer porous spherical structure carbon material to treat low-concentration Cr(VI) waste liquid, and having faster adsorption kinetics during adsorption (in a 50 mg / L Cr(VI) solution, it can reach 77.59-99.58 mg / g in 48 hours), and in most cases, when adsorbing low-concentration Cr(VI) wastewater, it can achieve complete adsorption and removal of Cr(VI).
[0022] (2) The method for preparing the porous double-layer spherical carbon material provided by the present invention has a simple process and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a TEM image of the porous double-layer spherical structure carbon material prepared in Example 1; Figure 2 This is a TEM image of the porous double-layer spherical structure carbon material prepared in Example 2; Figure 3 This is a TEM image of the porous double-layer spherical structure carbon material prepared in Example 3; Figure 4 This is a TEM image of the porous double-layer spherical structure carbon material prepared in Example 4; Figure 5 This is a TEM image of the porous double-layer spherical structure carbon material prepared in Example 5; Figure 6 This is a TEM image of the porous double-layer spherical structure carbon material prepared in Example 6; Figure 7 This is a TEM image of the porous double-layer spherical structure carbon material prepared in Example 7; Figure 8 This is a TEM image of the porous double-layer spherical carbon material prepared in Comparative Example 1; Fig. 9 This is a TEM image of the porous double-layer spherical carbon material prepared in Comparative Example 2; Fig.10 The adsorption kinetic curves of hexavalent chromium by the carbon materials prepared in Examples 1 to 7 and Comparative Examples 1 to 2; Fig.11 and Fig.12 N is the carbon material prepared in Examples 1 to 7 and Comparative Examples 1 to 2. 2 Adsorption-desorption isotherms; Fig.13 ] is the pore size distribution curve of the carbon material prepared in Examples 1 to 4. DETAILED DESCRIPTION
[0024] The present invention is further described in conjunction with the following examples.
[0025] The raw materials and reagents involved in the examples of the present invention can be obtained from commercial channels. The amount of each component is expressed in parts by mass and parts by volume, 1 part by mass: 1 part by volume = 1 g / mL.
[0026] Example 1 50 parts by volume of anhydrous ethanol and 2.5 parts by volume of ammonia water were mixed and stirred for 20 minutes, and then 0.4 parts by volume of resorcinol and 0.56 parts by volume of 37% formaldehyde solution were added, and stirred at 25°C for 6 hours, and 2 parts by volume of tetraethyl orthosilicate were added. After stirring for 24 hours, the solution was transferred to an 80mL hydrothermal kettle, and hydrothermally treated at 100°C for 24 hours, and the precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and dried in a drying oven at 60°C for 12 hours to obtain a brown powder. Subsequently, the temperature was raised to 200°C at 3°C / min in a nitrogen atmosphere in a tubular furnace and maintained for 2 hours, and then the temperature was continued to be raised to 700°C at 3°C / min and maintained for 2 hours to obtain a black powder. The obtained black powder was placed in 100 mL of 2 mol / L NaOH solution, stirred for 24 h, and then centrifuged to obtain the precipitate. After washing with deionized water three times and ethanol three times, the precipitate was dried in a drying oven at 60° C. for 12 h to obtain a porous double-layer spherical structure carbon material.
[0027] The morphology of the porous double-layer spherical carbon material prepared in this example is shown in the attached figure. Figure 1 Its pore structure parameters are shown in Table 1, and its specific surface area is 755.40m 2 / g, average pore diameter of 6.21nm, pore volume of 1.17cm 3 / g.
[0028] 50 mg of the porous double-layer spherical carbon material prepared above was added to 100 mL of 50 mg / L Cr(VI) solution. After 48 h, the adsorption amount of the porous double-layer spherical carbon material was 99.58 mg / g, the adsorption rate was 99.58%, and the residual Cr(VI) concentration was 0.21 mg / L. The adsorption curve is shown in FIG. Fig.10 .
[0029] 50 mg of the porous double-layer spherical structure carbon material prepared above was added to 100 mL of 10 mg / L Cr(VI) solution. After 24 hours, the adsorption amount of the porous double-layer spherical structure carbon material was 20 mg / g, the adsorption rate was 100%, and the residual Cr(VI) concentration was 0 mg / L.
[0030] Example 2 50 parts by volume of anhydrous ethanol and 2.5 parts by volume of ammonia water were mixed and stirred for 20 minutes, and then 0.4 parts by volume of resorcinol and 0.56 parts by volume of 37% formaldehyde solution were added, and stirred at 25°C for 4 hours, and 2 parts by volume of tetraethyl orthosilicate were added. After stirring for 26 hours, the solution was transferred to an 80mL hydrothermal kettle, and hydrothermally treated at 100°C for 24 hours, and the precipitate was collected by centrifugation. After washing with deionized water three times and ethanol three times, it was dried in a drying oven at 60°C for 12 hours, and a brown powder was collected. Subsequently, in a nitrogen atmosphere of a tube furnace, the temperature was raised to 200°C at 3°C / min and maintained for 2 hours, and then the temperature was continued to be raised to 700°C at 3°C / min and maintained for 2 hours to obtain a black powder. The obtained black powder was placed in 100 mL of 2 mol / L NaOH solution and stirred for 24 h, then the precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and then dried in a drying oven at 60° C. for 12 h to obtain a porous double-layer spherical structure carbon material.
[0031] The porous double-layer spherical carbon material prepared in this example has a surface morphology as shown in the attached figure. Figure 2 Its pore structure parameters are shown in Table 1, and its specific surface area is 547.93m 2 / g, average pore diameter of 5.11nm, pore volume of 0.70cm 3 / g.
[0032] 50 mg of the porous double-layer spherical carbon material prepared above was added to 100 mL of 50 mg / L Cr(VI) solution. After 48 h, the adsorption amount of the porous double-layer spherical carbon material was 91.09 mg / g, the adsorption rate was 91.09%, and the residual Cr(VI) concentration was 4.45 mg / L. The adsorption curve is shown in FIG. Fig.10 .
[0033] Take 50 mg of the porous double-layer spherical structure carbon material prepared above and add it to 100 mL, 10 mg / L Cr(VI) solution. After 24 hours, the adsorption amount of the porous double-layer spherical structure carbon material is 20 mg / g, the adsorption rate is 100%, and the residual Cr(VI) concentration is 0 mg / L.
[0034] Example 3 50 parts by volume of anhydrous ethanol and 2.5 parts by volume of ammonia water were mixed and stirred for 20 minutes, and then 0.4 parts by mass of resorcinol and 0.56 parts by volume of 37% formaldehyde solution were added, and stirred at 25°C for 8 hours, and 2 parts by volume of tetraethyl orthosilicate were added. After stirring for 22 hours, the solution was transferred to an 80mL hydrothermal kettle, and hydrothermally treated at 100°C for 24 hours, and the precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and dried in a drying oven at 60°C for 12 hours to obtain a brown powder. Subsequently, the temperature was raised to 200°C at 3°C / min in a nitrogen atmosphere in a tubular furnace and maintained for 2 hours, and then the temperature was continued to be raised to 700°C at 3°C / min and maintained for 2 hours to obtain a black powder. The obtained black powder was placed in 100 mL of 2 mol / L NaOH solution and stirred for 24 h, then the precipitate was collected by centrifugation, washed three times with deionized water and three times with ethanol, and dried in a drying oven at 60° C. for 12 h to obtain a porous double-layer spherical structure carbon material.
[0035] The porous double-layer spherical carbon material prepared in this example has a surface morphology as shown in the attached figure. Figure 3 Its pore structure parameters are shown in Table 1, and its specific surface area is 525.31m 2 / g, average pore diameter of 5.50nm, pore volume of 0.72cm 3 / g.
[0036] 50 mg of the porous double-layer spherical carbon material prepared above was added to 100 mL of 50 mg / L Cr(VI) solution. After 48 h, the adsorption amount of the porous double-layer spherical carbon material was 80.29 mg / g, the adsorption rate was 80.29%, and the residual Cr(VI) concentration was 10.35 mg / L. The adsorption curve is shown in FIG. Fig.10 .
[0037] 50 mg of the porous double-layer spherical structure carbon material prepared above was added to 100 mL of 10 mg / L Cr(VI) solution. After 24 hours, the adsorption amount of the porous double-layer spherical structure carbon material was 19.38 mg / g, the adsorption rate was 96.92%, and the residual Cr(VI) concentration was 0.308 mg / L. After 48 hours, the adsorption amount of the porous double-layer spherical structure carbon material was 20 mg / g, the adsorption rate was 100%, and the residual Cr(VI) concentration was 0 mg / L.
[0038] Example 4 50 parts by volume of anhydrous ethanol and 2.5 parts by volume of ammonia water were mixed and stirred for 20 minutes, and then 0.4 parts by volume of resorcinol and 0.56 parts by volume of 37% formaldehyde solution were added, and stirred at 25°C for 6 hours, and 1 part by volume of tetraethyl orthosilicate was added. After stirring for 24 hours, the solution was transferred to an 80mL hydrothermal kettle, and hydrothermally treated at 100°C for 24 hours, and the precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and dried in a drying oven at 60°C for 12 hours to obtain a brown powder. Subsequently, the temperature was raised to 200°C at 3°C / min in a nitrogen atmosphere in a tubular furnace and maintained for 2 hours, and then the temperature was continued to be raised to 700°C at 3°C / min and maintained for 2 hours to obtain a black powder. The obtained black powder was placed in 100 mL of 2 mol / L NaOH solution and stirred for 24 h, then the precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and then dried in a drying oven at 60° C. for 12 h to obtain a porous double-layer spherical structure carbon material.
[0039] The morphology of the porous double-layer spherical carbon material prepared in this example is shown in the attached figure. Figure 4 Its pore structure parameters are shown in Table 1, and its specific surface area is 648.94m 2 / g, average pore diameter of 5.44nm, pore volume of 0.88cm 3 / g.
[0040] 50 mg of the porous double-layer spherical carbon material prepared above was added to 100 mL of 50 mg / L Cr(VI) solution. After 48 h, the adsorption amount of the porous double-layer spherical carbon material was 91.63 mg / g, the adsorption rate was 91.63%, and the residual Cr(VI) concentration was 4.18 mg / L. The adsorption curve is shown in FIG. Fig.10 .
[0041] Take 50 mg of the porous double-layer spherical structure carbon material prepared above and add it to 100 mL, 10 mg / L Cr(VI) solution. After 24 hours, the adsorption amount of the porous double-layer spherical structure carbon material is 20 mg / g, the adsorption rate is 100%, and the residual Cr(VI) concentration is 0 mg / L.
[0042] Example 5 50 parts by volume of anhydrous ethanol and 2.5 parts by volume of ammonia water were mixed and stirred for 20 minutes, and then 0.4 parts by volume of resorcinol and 0.56 parts by volume of 37% formaldehyde solution were added, and stirred at 25°C for 6 hours, and 3 parts by volume of tetraethyl orthosilicate were added. After stirring for 24 hours, the solution was transferred to an 80mL hydrothermal kettle, and hydrothermally treated at 100°C for 24 hours, and the precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and dried in a drying oven at 60°C for 12 hours to obtain a brown powder. Subsequently, the temperature was raised to 200°C at 3°C / min in a nitrogen atmosphere in a tubular furnace and maintained for 2 hours, and then the temperature was continued to be raised to 700°C at 3°C / min and maintained for 2 hours to obtain a black powder. The obtained black powder was placed in 100 mL of 2 mol / L NaOH solution and stirred for 24 h, then the precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and then dried in a drying oven at 60° C. for 12 h to obtain a porous double-layer spherical structure carbon material.
[0043] The porous double-layer spherical carbon material prepared in this example has a surface morphology as shown in the attached figure. Figure 5 Its pore structure parameters are shown in Table 1, and its specific surface area is 830.38m 2 / g, average pore diameter of 6.84nm, pore volume of 1.42cm 3 / g.
[0044] 50 mg of the porous double-layer spherical carbon material prepared above was added to 100 mL of 50 mg / L Cr(VI) solution. After 48 h, the adsorption amount of the porous double-layer spherical carbon material was 89.47 mg / g, the adsorption rate was 89.47%, and the residual Cr(VI) concentration was 5.27 mg / L. The adsorption curve is shown in FIG. Fig.10 .
[0045] Take 50 mg of the porous double-layer spherical structure carbon material prepared above and add it to 100 mL, 10 mg / L Cr(VI) solution. After 24 hours, the adsorption amount of the porous double-layer spherical structure carbon material is 20 mg / g, the adsorption rate is 100%, and the residual Cr(VI) concentration is 0 mg / L.
[0046] Example 6 50 parts by volume of anhydrous ethanol and 2.5 parts by volume of ammonia water were mixed and stirred for 20 minutes, and then 0.4 parts by volume of resorcinol and 0.56 parts by volume of 37% formaldehyde solution were added, and stirred at 25°C for 6 hours. 2 parts by volume of tetraethyl orthosilicate were added, and stirring was continued for 24 hours. The solution was transferred to an 80mL hydrothermal kettle, and hydrothermally treated at 100°C for 24 hours. The precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and dried in a drying oven at 60°C for 12 hours to obtain a brown powder. Subsequently, the temperature was raised to 200°C at 3°C / min in a nitrogen atmosphere in a tubular furnace and maintained for 2 hours, and then the temperature was continued to be raised to 600°C at 3°C / min and maintained for 2 hours to obtain a black powder. The obtained black powder was placed in 100 mL of 2 mol / L NaOH solution and stirred for 24 h, then the precipitate was collected by centrifugation, washed three times with deionized water and three times with ethanol, and dried in a drying oven at 60° C. for 12 h to obtain a porous double-layer spherical structure carbon material.
[0047] The porous double-layer spherical carbon material prepared in this example has a surface morphology as shown in the attached figure. Figure 6 Its pore structure parameters are shown in Table 1, and its specific surface area is 634.36m 2 / g, average pore diameter of 5.91nm, pore volume of 0.93cm 3 / g.
[0048] 50 mg of the porous double-layer spherical carbon material prepared above was added to 100 mL of 50 mg / L Cr(VI) solution. After 48 h, the adsorption amount of the porous double-layer spherical carbon material was 92.84 mg / g, the adsorption rate was 92.84%, and the residual Cr(VI) concentration was 3.58 mg / L. The adsorption curve is shown in FIG. Fig.10 .
[0049] Take 50 mg of the porous double-layer spherical structure carbon material prepared above and add it to 100 mL, 10 mg / L Cr(VI) solution. After 24 hours, the adsorption amount of the porous double-layer spherical structure carbon material is 20 mg / g, the adsorption rate is 100%, and the residual Cr(VI) concentration is 0 mg / L.
[0050] Example 7 50 parts by volume of anhydrous ethanol and 2.5 parts by volume of ammonia water were mixed and stirred for 20 minutes, and then 0.4 parts by volume of resorcinol and 0.56 parts by volume of 37% formaldehyde solution were added, and stirred at 25°C for 6 hours. 2 parts by volume of tetraethyl orthosilicate were added, and stirring was continued for 24 hours. The solution was transferred to an 80mL hydrothermal kettle, and hydrothermally treated at 100°C for 24 hours. The precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and dried in a drying oven at 60°C for 12 hours to obtain a brown powder. Subsequently, the temperature was raised to 200°C at 3°C / min in a nitrogen atmosphere in a tubular furnace and maintained for 2 hours, and then the temperature was continued to be raised to 800°C at 3°C / min and maintained for 2 hours to obtain a black powder. The obtained black powder was placed in 100 mL of 2 mol / L NaOH solution and stirred for 24 h, then the precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and then dried in a drying oven at 60° C. for 12 h to obtain a porous double-layer spherical structure carbon material.
[0051] The porous double-layer spherical carbon material prepared in this example has a surface morphology as shown in the attached figure. Figure 7 Its pore structure parameters are shown in Table 1, and its specific surface area is 248.84m 2 / g, average pore diameter of 6.16nm, pore volume of 0.38cm 3 / g.
[0052] 50 mg of the porous double-layer spherical carbon material prepared above was added to 100 mL of 50 mg / L Cr(VI) solution. After 48 h, the adsorption amount of the porous double-layer spherical carbon material was 77.59 mg / g, the adsorption rate was 77.59%, and the residual Cr(VI) concentration was 11.21 mg / L. The adsorption curve is shown in FIG. Fig.10 .
[0053] 50 mg of the porous double-layer spherical structure carbon material prepared above was added to 100 mL of 10 mg / L Cr(VI) solution. After 24 hours, the adsorption amount of the porous double-layer spherical structure carbon material was 16.54 mg / g, the adsorption rate was 82.73%, and the residual Cr(VI) concentration was 1.73 mg / L. After 48 hours, the adsorption amount of the porous double-layer spherical structure carbon material was 19.72 mg / g, the adsorption rate was 98.6%, and the residual Cr(VI) concentration was 0.14 mg / L.
[0054] Comparative Example 1 50 parts by volume of anhydrous ethanol and 2.5 parts by volume of ammonia water were mixed and stirred for 20 minutes, and then 0.4 parts by mass of resorcinol, 0.56 parts by volume of 37% formaldehyde solution, and 2 parts by volume of tetraethyl orthosilicate were added. After stirring at 25°C for 30 hours, the solution was transferred to an 80mL hydrothermal kettle, and hydrothermally treated at 100°C for 24 hours. The precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and dried in a 60°C drying oven for 12 hours to obtain a brown powder. Subsequently, in a nitrogen atmosphere of a tubular furnace, the temperature was raised to 200°C at 3°C / min and maintained for 2 hours, and then continued to be raised to 800°C at 3°C / min and maintained for 2 hours to obtain a black powder. The obtained black powder was placed in 100mL, 2mol / L NaOH solution and stirred for 24 hours, and the precipitate was collected by centrifugation. After three deionized water and three ethanol washes, it was dried in a 60°C drying oven for 12 hours to obtain hollow carbon spheres.
[0055] The apparent morphology of the hydrothermal carbon prepared in this example is shown in the attached figure. Fig. 9 As shown, it is a hollow carbon sphere; its pore structure parameter data are shown in Table 1, and the specific surface area is 430.80m 2 / g, average pore diameter of 4.90nm, pore volume of 0.53cm 3 / g.
[0056] 50 mg of the hollow carbon sphere sample prepared above was added to 100 mL of 50 mg / L Cr(VI) solution. After 48 h, the adsorption amount of Cr(VI) by the hollow carbon sphere was 67.29 mg / g, the adsorption rate was 67.29%, and the residual Cr(VI) concentration was 16.35 mg / L. The adsorption curve is shown in Figure 2. Fig.10 .
[0057] 50 mg of the hollow carbon sphere sample prepared above was added to 100 mL of 10 mg / L Cr(VI) solution. After 24 h, the adsorption amount of Cr(VI) by the hollow carbon sphere was 16.64 mg / g, the adsorption rate was 83.21%, and the residual Cr(VI) concentration was 1.68 mg / L; after 48 h, the adsorption amount of Cr(VI) by the hollow carbon sphere was 19.6 mg / g, the adsorption rate was 98.04%, and the residual Cr(VI) concentration was 0.20 mg / L.
[0058] Comparative Example 2 50 parts by volume of anhydrous ethanol and 2.5 parts by volume of ammonia water were mixed and stirred for 20 minutes, and then 0.4 parts by mass of resorcinol and 0.56 parts by volume of 37% formaldehyde solution were added. After stirring at 25°C for 30 hours, the solution was transferred to an 80mL hydrothermal kettle, and after hydrothermal treatment at 100°C for 24 hours, the precipitate was collected by centrifugation, washed with deionized water three times and ethanol three times, and dried in a 60°C drying oven for 12 hours to obtain a brown powder. Subsequently, in a nitrogen atmosphere of a tubular furnace, the temperature was raised to 200°C at 3°C / min and maintained for 2 hours, and then continued to be raised to 800°C at 3°C / min and maintained for 2 hours to obtain a black powder. The obtained black powder was placed in 100mL, 2mol / L NaOH solution and stirred for 24 hours, and the precipitate was collected by centrifugation. After three deionized water and three ethanol washes, it was dried in a 60°C drying oven for 12 hours to obtain solid carbon spheres.
[0059] The morphology of the hydrothermal carbon prepared in this example is shown in the attached figure. Figure 8 As shown, it is a solid carbon sphere; its pore structure parameters are shown in Table 1, and the specific surface area is 299.16m 2 / g, average pore diameter of 2.14nm, pore volume of 0.16cm 3 / g.
[0060] 50 mg of the solid carbon ball sample prepared above was added to 100 mL of 50 mg / L Cr(VI) solution. After 48 h, the adsorption amount of Cr(VI) by the solid carbon ball was 26.2 mg / g, the adsorption rate was 26.2%, and the residual Cr(VI) concentration was 36.9 mg / L. The adsorption curve is shown in Figure 2. Fig.10 .
[0061] 50 mg of the solid carbon ball sample prepared above was added to 100 mL of 10 mg / L Cr(VI) solution. After 24 h, the adsorption amount of Cr(VI) by the solid carbon ball was 6.98 mg / g, the adsorption rate was 34.89%, and the residual Cr(VI) concentration was 6.51 mg / L; after 48 h, the adsorption amount of Cr(VI) by the solid carbon ball was 8.36 mg / g, the adsorption rate was 41.79%, and the residual Cr(VI) concentration was 5.82 mg / L.
[0062] Table 1 Pore structure parameters of carbon materials prepared in Examples 1-7 and Comparative Examples 1-2 Table 2 Adsorption data of low concentration Cr(VI) wastewater by carbon materials prepared in Examples 1-7 and Comparative Examples 1-2 Adsorption conditions in Table 2: 0.05 g of carbon ball sample was added to 100 mL of 10 mg / L Cr(VI) solution and adsorbed in an oscillating box (setting conditions: 150 rpm, 25°C).
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a porous double-layer spherical carbon material, characterized in that: The following steps are involved: (1) Mixing and stirring a carbon source and ammonia water, then adding a silicon source, and then transferring the reaction mixture to a hydrothermal kettle for hydrothermal reaction. After the reaction is completed, cooling and separating the product to obtain a brown powder; wherein the carbon source is resorcinol and formaldehyde solution, and the amount ratio of resorcinol, formaldehyde solution, ammonia water, silicon source and ethanol is 1 mass part: (1-3) volume parts: (4-10) volume parts: (2.5-7.5) volume parts: 125 volume parts, 1 mass part: 1 volume part = 1g / mL; (2) calcining the brown powder obtained in step (1) in a protective atmosphere to obtain a black powder; (3) The black powder obtained in step (2) is added to an alkaline solution for etching, and a hollow middle layer is formed after etching the silicon dioxide, thereby obtaining the porous double-layer spherical structure carbon material.
2. The preparation method according to claim 1, characterized in that: In step (1), the carbon source and ammonia water are mixed and stirred for 4-8 hours.
3. The preparation method according to claim 1, characterized in that: After adding the silicon source in step (1), stirring is continued for 22 to 26 hours, and then the reaction mixture is transferred to a hydrothermal kettle for hydrothermal reaction; the silicon source is tetraethyl orthosilicate.
4. The preparation method according to claim 1, characterized in that: The formaldehyde solution in step (1) is a 37 wt % formaldehyde aqueous solution containing 10-15 wt % methanol stabilizer.
5. The preparation method according to claim 1, characterized in that: The hydrothermal reaction in step (1) is carried out at 100° C. for 24 h.
6. The preparation method according to claim 1, characterized in that: The first stage of the two-stage calcination in step (2) is calcined at 200°C for 2h, and the second stage is calcined at 600-800°C for 2h; the heating rate of the two-stage calcination is 3°C / min, the protective atmosphere is nitrogen, and the nitrogen flow rate is 50mL / min.
7. The preparation method according to claim 1, characterized in that: The alkaline solution in step (3) is a 2 mol / L NaOH solution, and the etching time is 24 h.
8. A porous double-layer spherical structure carbon material prepared by the method according to any one of claims 1 to 7.
9. The porous double-layer spherical structure carbon material according to claim 8, characterized in that: Its specific surface area is 248.84~830.38m 2 / g, the particle size range is 200~500nm, the wall thickness is 50~100nm; the inner core is a non-uniform spherical particle with a diameter of 10~50nm.
10. Use of the porous double-layer spherical structure carbon material according to claim 8 or 9 for adsorbing Cr(VI) in water.
